Gut microbiota and risk of endocarditis: a bidirectional Mendelian randomization study - Yang, Mengyue; Bi, Wen; Zhang, Zhijie (Frontiers in Microbiology, 2024)
The associations between gut microbiota and cardiovascular disease have been reported in previous studies. However, the relationship between gut microbiota and endocarditis remains unclear.Methods: A bidirectional Mendelian randomization (MR) study was performed to detect the association between gut microbiota and endocarditis. Inverse variance weighted (IVW) method was considered the main result. Simultaneously, heterogeneity and pleiotropy tests were conducted.Results: Our study suggests that family Victivallaceae (P=0.020), genus Eubacterium fissicatena group (P=0.047), genus Escherichia Shigella (P=0.024), genus Peptococcus (p=0.028) and genus Sellimonas (p=0.005) play protective roles in endocarditis. Two microbial taxa, including genus Blautia (p=0.006) and genus Ruminococcus2 (p=0.024) increase the risk of endocarditis. At the same time, endocarditis has a negative effect on genus Eubacterium fissicatena group (p=0.048).Besides，no heterogeneity or pleiotropy was found in this study.Our study emphasized the certain role of specific gut microbiota in patients with endocarditis and clarified the negative effect of endocarditis on gut microbiota.